Letramento literário : a escola como espaço privilegiado para formação de leitores - Souza, Dalma Flávia Barros Guimarães de (2015)
This research focuses in the area of languages and literacy and is in line with the precepts of the literary literacy. The proposal named \"literary Literacy: the school as a privileged space for the formation of readers\" aims to strengthen and expand the General form the literary education in the elementary school, transforming the school into a community of readers, that transcends its walls and develop in the student reading skills of the world and of himself. To this end, we draw up and apply two didactic proposals (basic sequence and reading circle) to the reading of literary books: \"6 times Lucas\" and \"the hug\", Lygia Bojunga Nunes, in a class of eighth grade of elementary school of the public school, in the town of Rio Verde, Goiás. To achieve the proposed objectives, we made, a priori, a bibliographical study to theoretically and build three theoretical chapters. We use, too, another chapter to explain some choices relevant to our research. Thus, our research has ethnographic character based, methodologically, from the perspective of action research, using as instruments of data collection: initial diagnosis, exercises of basic sequence for the literary work \"6 times Lucas\", tokens, chips to read records from the circle of literary reading \"the hug\", wheels of conversation; final diagnosis and personal records of teacher/researcher. From the data collected, we have written our chapter the material analysis, with emphasis on the reception of students in relation to activities we prepared and mediated, in order to promote the recovery of literature in the classroom. Thus, within the limits of this research, we can say that each proposed activity on basic sequence and in the reading circle contributed to drive the process of literary literacy teacher, encouraging readings of aesthetic quality, identify two methodologies to prioritize reading and literary textreader interaction and form a community of readers by means of adequate schooling literature.